Development of a Caregiver Mindset Scale in Caregivers of Persons with Dementia - DeBraal, Jordyn M. (My University, 2019)
A growth mindset is defined as the belief that one’s basic traits and abilities can be improved upon through continuing effort and learning. In contrast, a fixed mindset is the belief that one’s qualities are inborn and unchangeable, which creates a motivation to avoid negative feedback and respond negatively to failure (Dweck, 2006). The mindset that a caregiver of a family member with dementia holds can influence how they approach caregiving duties for persons in their care. The aim of the current study was to develop a caregiver mindset scale designed to assess the growth and fixed mindsets of people engaged in informal family caregiving of a person with dementia. A concept analysis and literature review was conducted with the goal of developing a scale that measures the mindsets of informal caregivers. Data from 355 family caregivers who were taking care of their family member with dementia at home were collected on Amazon Mechanical Turk. An exploratory factor analysis was performed to uncover the underlying factor structure in the data, and more specifically, to test for the presence of a caregiver growth mindset and a caregiver fixed mindset. The final DCM Scale contained 33 items, which measured a variety of caregiving beliefs regarding growth mindset domains of content, dementia caregiver specific growth skills, and caregiver relationship skills that were organized into two factors. The caregiver growth mindset factor consisted of 22 items (α = 0.90) and the caregiver fixed mindset factor consisted of 11 items (α = 0.88), demonstrating excellent internal consistency. Future research should aim to test further the psychometric properties of this dementia caregiver mindset scale.
Keywords: Growth mindset; Dementia; Caregiver